A primer for swimming coaches. Volume 1: Physiological foundations - Maglischo, E. W. (Sports and athletics preparation, performance, and psychology, 2015)
Book Description: It has been 12 years since the author published the 3rd edition of the Swimming Faster series and time has not stood still. Research has continued at a rapid pace, using increasingly sophisticated methodology to improve our knowledge of the training process. In this book, the author shares what he learned with members of the competitive swimming community throughout the world.